2013
DOI: 10.1098/rspb.2013.1671
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between two intestinal parasites in humans: the importance of co-infection for infection risk and recovery dynamics

Abstract: Co-infection may affect transmission and recovery from infection, but remains an understudied element of disease ecology, particularly with regard to antagonism between parasites sharing a host. Helminth and giardia infections are often endemic in the same populations and both occupy the small intestine; yet few studies have examined interactions between these parasites. We report on helminth -giardia co-infections in a panel study of forager -horticulturalists in the Bolivian lowlands. Parasites were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 28 publications
2
78
0
2
Order By: Relevance
“…Tsimane' children and adults have a 56-80 % prevalence of parasitic helminthic infections (10,11) . Infectious diseases, including GI infection, historically have accounted for more than 50 % of all deaths (45) .…”
Section: Background and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsimane' children and adults have a 56-80 % prevalence of parasitic helminthic infections (10,11) . Infectious diseases, including GI infection, historically have accounted for more than 50 % of all deaths (45) .…”
Section: Background and Methodsmentioning
confidence: 99%
“…The paper focuses on Tsimane' because they lack access to clean water, yet are highly active and live in a hot, humid environment, creating high water needs. Additionally, previous research has documented high prevalences of water-related diarrhoeal diseases and parasitic infection (10,11) . …”
mentioning
confidence: 99%
“…In turn, these can have significant impacts on epidemiology [8][9][10][11][12], with major repercussions for disease control in humans [13,14] and other animal hosts [15]. For example, rodents infected with multiple Plasmodium sp.…”
Section: Introductionmentioning
confidence: 99%
“…Although albendazole or mebendazole have been the mainstay of therapy against hookworm since times long past, a study by Blackwell et al concluded that antiprotozoal agents may provide short-term benefits, but do not appear to have lasting effects due to constant reinfection. 15 An effective treatment for either parasite is not likely without a coalition of short-term therapy and long-term improvements in sanitation systems and access to clean drinking water besides health awareness amongst the masses. …”
Section: Discussionmentioning
confidence: 99%